Wewenang Pemerintah dalam Perlindungan Hukum bagi Orang Atau Badan yang Menyelenggarakan Pembangunan Perumahan dalam Undang-Undang Nomor 1 Tahun 2011 Tentang Perumahan dan Kawasan Permukiman - Dimas Purnayoga Rakayoni; Subekti Subekti; Ernu Widodo (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
That housing and settlement development by private business entities is compatible with the Sustainable Development Goals (SDGs) or can also be called Sustainable Development Goals (SDGs) is a sustainable development agenda initiated and agreed upon by the United Nations. Meanwhile, the construction of houses by individuals or individuals is very inconsistent with the programs or agendas set forth by the national and world governments. Of course, if we examine further, the development carried out by each person is very contrary to "participating in implementing world order" as described in the preamble to the 1945 Constitution of the Republic of Indonesia. The legal issue of this normative legal research: What is the government's authority in the implementation of housing development? How is the legal protection for people or entities that organize housing development in Law Number 1 of 2011 concerning Housing and Residential Areas? The government's authority in the implementation of housing development includes policy regulation, implementation supervision, housing provision facilitation, inter- government coordination, community empowerment, and education. Through this authority, the government seeks to create a decent and sustainable residential environment for all levels of society. Legal protection for persons or entities that organize housing development is comprehensively regulated in Law No. 1 of 2011 concerning Housing and Residential Areas. Legal protection includes: 1. Community Rights. 2. Developer's Obligations. 3. Sanctions for Violations. 4. The Role of the Government.